History of one documents and not only... - Kuodytė, Dalia (Genocidas ir rezistencija, 2000)
The purpose of this publication is to present a document that may be of relevance for the investigation of the activities of the Lithuanian provisional government formed on 22 June 1941. It is a letter from Mečislovas Mackevičius, the former Minister of Justice of the provisional government, to Dr Domas Jasaitis, referring to the “Regulations on the Jewish question”, which is considered to be one of the most infamous documents of the provisional government, not only in Lithuanian historiography, and which unambiguously expresses the anti–Semitic sentiments of the members of the provisional government and the character of the government itself. It should be noted here that the Regulations in question are not the only document adopted by the provisional government postulating Jewish discrimination. Therefore, this publication does not intend to change the fundamental assessments, but only to draw attention to the need to work more carefully with the sources and to evaluate them more critically, especially in relation to such a complex period of Lithuanian history as June 1941.